Inmunohistoquímica en Lesiones Cutáneas Melanociticas: Utllidad de los Marcadores Antígeno S100, HMB-45, Cromogranina A y Proteína p53 - Barrionuevo, Carlos (1999)
OBJECTIVES: To determine the clinicopathological features of patients with cutaneous melanoma, the role of Merckel cells in this tumour and diagnostic usefulness of celular markers. MATERIAL AND METHODS: Clinico-pathological correlation of 650 clinical records of patients with histopathological diagnosis of cutaneous melanoma was done. The Ag S100, HMB-45, cromogranin A, and p53 protein presence were assessed in 30 of these patients who also had pigmented benign skin lesions. RESULTS: Patients with melanoma had history of sunlight exposure and previous nevus or associated nevus. AgS100 was the more sensitive marker but had lesser specificity; HMB-45 was positive in lesions with malignant and active melanocytes whereas p53 was seen in certain melanoma cells. Proliferating Merckel cells were not found. CONCLUSIONS: S100 antigen must be used as diagnostic tool; HMB-45 had a lesser sensitivity. Melanomas, displasic nevus cells and sunlight dermatosis queratinocites were all p53-positive.